ACTUALIZATION OF UKRAINIAN AND TURKISH MILITARY MEDICINES COOPERATION: FROM THE HISTORY OF RELATIONS BETWEEN THE UKRAINIAN MILITARY MEDICAL ACADEMY AND THE GULHANE MILITARY MEDICAL ACADEMY OF THE TURKISH ARMED FORCES - Mykhailo BADIUK; Iryna PASKO; Valeriy SOLYARIK; Yuriy SKALETSKY; Tatyana SYKYRYTSKA (Актуальні питання суспільних наук та історії медицини, 2020)
The purpose of the study is aimed at a comprehensive analysis of materials highlighting the specific results of cooperation between Ukrainian Military Medical Academy (UMMA) and medical services of the NATO countries, which has almost quarter-century history, since the mid-1990s, and in which the medical service of the Turkish Armed Forces occupies a leading position. Materials and methods. The information base of the article includes the materials of official bilateral visits between the leaders of medical services of the Armed Forces of Ukraine and the Turkish Republic, and between the Ukrainian Military Medical Academy and the Gulhane Military Medical Academy (Ankara) at 1997-2000. A unique illustrative content (photographic materials) is included, which is verifying the documents and data used in the article. Results. The article describes in details of the visit program and their practical implementation. Based on the specific results of professional relationships between Ukrainian and Turkish military medical specialists their scientific and practical significance and relevance have been demonstrated. Conclusions. Active organizational